Temperature and shear stress in thin film EHD contacts - Grieve,RSA; Spikes,HA (Tribology Series, 2000)
There is growing need to understand the origins and magnitude of friction in elastohydrodynamic (EHD) conditions, both to minimise it in some applications, and thus to save energy, but also to maximise and predict it in traction drive applications. Such an understanding requires an accurate model of the rheological properties of lubricant under EHD contact conditions. This paper first reviews the main methods for studying EHD rheology. It then focuses on a technique for obtaining maps of shear stress and thus friction across EHD contacts. An infrared microscope is used to measure surface temperatures in a lubricated rolling-sliding, steel ball on sapphire disc contact. From these measurements, maps of the variation of shear stress of the fluid film over the contact are derived using moving heat source analysis. These maps provide information on how both shear stress and temperature vary across a contact. © 2000 Elsevier Science B.V. All rights reserved.